Do Higher Levels of Qualification Lead to Higher Returns to Education: Evidence from Malaysian Education Sector - Yunus, Norhanishah Mohamad; Said, Rusmawati (International Journal of Economics and Financial Issues, 2016)
Using data from a Household Income Survey (HIS), this study provides first evidence about returns to education at highest certificates of qualification in the Malaysian Education sector. We employ a simple Ordinary Least Squares (OLS) estimator with robust standard errors to estimate the Mincerian equation during the years 2002–2007. Our results show that workers with degree qualifications have high average returns, followed by diploma-educated workers during the period investigation. The results indicate that the returns to education show a linear relationship between certificates of qualification and earnings. For policy makers with scarce resources to allocate between competing policies, the findings from the returns to education at highest certificates of qualification provides valuable information for the decision to provide extra funds for education. This results is also may act as a useful indicator for individuals to invest in their own human capital. Keywords: returns to education, earnings; certificates of qualification JEL Classifications: I26; J20, J30